2016 International Conference on Information Networking (ICOIN) 2016
DOI: 10.1109/icoin.2016.7427085
|View full text |Cite
|
Sign up to set email alerts
|

Selection of relay UE with energy harvesting capabilities in public safety environment

Abstract: Relaying is a widely proposed solution for multihop communication in PS environments. However, the selected relay is energy constrained and cannot go on indefinitely. Energy harvesting can solve this problem and make multi-hop D2D communication a viable solution for PS services. In this paper, selection of energy harvesting relay has been studied for deviceto-device (D2D) communications. Public safety environment has been considered, where some user equipments (UE) are located out of the coverage area of eNode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The energy efficient device-to-device (D2D) communication [269] constitutes a pivotal element of the 5G architecture. D2D networks are capable of accommodating more simultaneous communication pairs, of increasing the network capacity and of improving the bandwidth and energy efficiency [270]. A social-ware energy harvesting assisted device-to-device architecture was proposed in [271].…”
Section: A Distributed Idensmentioning
confidence: 99%
“…The energy efficient device-to-device (D2D) communication [269] constitutes a pivotal element of the 5G architecture. D2D networks are capable of accommodating more simultaneous communication pairs, of increasing the network capacity and of improving the bandwidth and energy efficiency [270]. A social-ware energy harvesting assisted device-to-device architecture was proposed in [271].…”
Section: A Distributed Idensmentioning
confidence: 99%
“…Although in [26,51], the EE issue has been considered, the multi-hop D2D communication was neglected, and the application scenario is different from our study. Considering the energy efficiency problem, the purpose of the original four-dimensional matching among D2D pairs, relay selections and resource blocks (RBs) reused in the first and second hop of two-hop D2D links is to maximize the EE of D2D links.…”
Section: Related Workmentioning
confidence: 99%
“…In [51], the selection of the energy harvesting relay has been studied for D2D communications in a public safety environment. In [23], the iterative Hungarian method was devised to solve the associated relay selection and resource assignment problems, and it showed that the optimal power allocation problem can be solved in a closed-form.…”
Section: Related Workmentioning
confidence: 99%
“…Also, a closed-form expression for the outage probability was derived to explore the effect of network parameters on it. Based on the PS protocol, the authors in [47] proposed a public safety approach that enabled the devices out of the BS coverage to communicate with each other in a relay-aided D2D communication manner. In addition, the relays were considered to harvest energy from the RF signal received from the BS.…”
Section: Introductionmentioning
confidence: 99%